Analysis of metagenomics data - Vasquez Christodoulou, Marlen (My University, 2026)
▪ Pipeline selection (Blast and Usearch workflow) ▪ Basic steps of analysis (barcode extraction, pick OTU, chimera identification and elimination, OTU table preparation, alignment and tree preparation) Prof. Luciana Migliore ERASMUS+ Staff Training Mobility